G442(P) What do looked after young people think about the specialist health services they use?. (27th April 2015) - Sunderland, E; Wood, K; Barwick, S
Abstract : Aim: There is limited research concerning the experiences, preferences and priorities of looked after children and young people (LACYP) relating to healthcare. LACYP have higher rates of physical, developmental and mental health problems than their peers, with worse longer–term outcomes. This study aims to capture young people's views on health and mental health services specifically for LACYP. Method: A questionnaire was created, incorporating issues identified as important to LACYP in existing literature, and modified with input from involved health and social care professionals and a LACYP participation group. Two LACYP health services and one LACYP mental health service were investigated over a four month period. All LACYP, aged 12 years and over, who attended for an initial or review health assessment or for specialist mental health services were given a questionnaire to complete anonymously in relation to their appointment. Results: 136 questionnaires were completed. Mean age of participants was 15.1 years (range 12–18), with equal numbers of males and females. 92% were glad they had attended their appointment, 99% felt listened to, 95% thought professionals were easy to talk to and 97% considered their views were taken seriously. 8% were not offered an opportunity to speak with the practitioner alone, but 73% of this group would not have wanted to do so. 7% worried about who would see the information given. Free text comments corresponded closely to key themes regarded by LACYP as important in existing literature; LACYP want to talk to professionals who listen and have an ability to get things done. Conclusion: It is clear the majority felt these services helped them; this is particularly relevant to health appointments where LACYP are not referred with a specific problem, but for statutory review. Recommendations include all LACYP being offered opportunities to speak with practitioners alone and ensuring confidentiality is discussed at the beginning of appointments. Acting on the results of this study forms the first step in ensuring local services meet the needs of LACYP more effectively.